Trait and state effects of different modes of thinking on salivary cortisol in daily life in patients with recurrent major depression and healthy individuals - Schricker, Isabelle; Nayman, Sibel; Reinhard, Iris; Kühner, Christine (Psychoneuroendocrinology, 2023)
Habitual modes of thinking such as repetitive negative thinking (RNT), but also momentary cognitive processes such as mindwandering could be vulnerability factors for the course of Major Depressive Disorder (MDD). On the physiological level, cortisol represents an important biological stress marker of the hypothalamic-pituitary-adrenal (HPA) axis. Being a dynamic and non-invasive measure, salivary cortisol can be assessed in daily life via Ambulatory Assessment (AA). So far, consensus exists on a dysregulation of the HPA axis in MDD. However, findings are ambiguous and AA-studies examining both trait and state level effects of cognitive processes on cortisol release in daily life in patients with recurrent major depression (rMDD) and healthy controls (HCs) are lacking. A sample of 119 (nrMDD=57, nHCs=62) participants underwent a baseline session, including self-rated questionnaires (RNT, mindfulness) followed by a 5-day AA, where participants indicated the occurrence of mindwandering and levels of mentalshift problems ten times per day via smartphone, and collected saliva cortisol samples five times per day. Via multilevel models, we found habitual RNT, but not mindfulness, to predict higher cortisol levels, with the effects being stronger in rMDD patients. State mindwandering and mentalshift problems predicted increased cortisol 20 min later across groups. State cognitions did not mediate the effects of habitual RNT on cortisol release. Our results suggest independent mechanisms of action for trait and state cognitions on cortisol activity in daily life and indicate a greater physiological vulnerability toward trait RNT and the tendency to experience mentalshift problems in patients with recurrent major depression.